The Personal and the Political in the Work of Mariama Bâ - Adele King (Studies in 20th & 21st Century Literature, 1994)
In her two novels, Une si longue lettre and Un Chant écarlate, Mariama Bâ describes how political as well as domestic problems develop from the tensions between tradition and the modern world. Desire for power and money leads to a post-independence society, in which greed motivates politicians and in which a woman is treated as merchandise to be purchased by the richest man. Adherence to a supposed ideal pre-colonial community, however, can lead to both the subjugation of women and political isolation. Bâ wants a morality based on respect for others, and a willingness to discard those traditions that inhibit such respect. She is critical of any separatism, between man and woman, black and white, European and African.
Keywords: Une si longue lettre; Un Chant écarlate; Mariama Bâ; political; political problems; domestic; domestic problems; tension; tradition; modern; modern world; post-independence; post-independence society; desire; money; power; greed; politicians; woman; property; pre-colonial community; subjugation of women; political isolation; morality; respect; critical; separatism; black and white; man and woman; European and African